2019
DOI: 10.1371/journal.pone.0213312
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and survey of Neisseria gonorrhoeae ceftriaxone and azithromycin susceptibility data in the Asia Pacific, 2011 to 2016

Abstract: Background Antimicrobial resistance in Neisseria gonorrhoeae is a global concern, with the ongoing emergence of ceftriaxone and azithromycin resistance threatening current treatment paradigms. To monitor the emergence of antimicrobial resistance in N . gonorrhoeae , the World Health Organization (WHO) Gonococcal Antimicrobial Surveillance Programme (GASP) has operated in the Western Pacific and South East Asian region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 81 publications
3
25
0
Order By: Relevance
“…ESCephalosporin AMR emerged rapidly in other organisms in the Asia Pacific region around the same time but, as was the case with N. gonorrhoeae, it did not spread uniformly throughout the region [42][43][44]. In the rural parts of Northern Territory, Australia, for example, there is almost no gonococcal resistance to ESCephalosporins or azithromycin, a finding that is likely attributable to low antimicrobial consumption [43,45]. Likewise, a phylogenetic analysis of 419 isolates from around the world found that modern gonococci were split into two lineages [41].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ESCephalosporin AMR emerged rapidly in other organisms in the Asia Pacific region around the same time but, as was the case with N. gonorrhoeae, it did not spread uniformly throughout the region [42][43][44]. In the rural parts of Northern Territory, Australia, for example, there is almost no gonococcal resistance to ESCephalosporins or azithromycin, a finding that is likely attributable to low antimicrobial consumption [43,45]. Likewise, a phylogenetic analysis of 419 isolates from around the world found that modern gonococci were split into two lineages [41].…”
Section: Discussionmentioning
confidence: 95%
“…At least in part, this was likely due to the extraordinary high ESCephalosporin consumption in Japan at the timeover double the consumption of the country with the next highest consumption [11]. ESCephalosporin AMR emerged rapidly in other organisms in the Asia Pacific region around the same time but, as was the case with N. gonorrhoeae, it did not spread uniformly throughout the region [42][43][44]. In the rural parts of Northern Territory, Australia, for example, there is almost no gonococcal resistance to ESCephalosporins or azithromycin, a finding that is likely attributable to low antimicrobial consumption [43,45].…”
Section: Discussionmentioning
confidence: 99%
“…ESCephalosporin AMR emerged rapidly in other organisms in the Asia Pacific region around the same time but, as was the case with N. gonorrhoeae, it did not spread uniformly throughout the region [36][37][38]. In the Northern Territory, Australia, for example, there is almost no gonococcal resistance to ESCephalosporins or azithromycin, a finding that is likely attributable to low antimicrobial consumption [37,39].…”
Section: Discussionmentioning
confidence: 96%
“…1 The WHO Gonococcal Antimicrobial Surveillance Programme (GASP) has operated in the Western Pacific and South East Asian regions since 1992, but surveillance of gonococcal antimicrobial resistance (AMR) remains limited in Asia Pacific. 6 A recent report showed that 18 of 21 countries in the region reported isolates with decreased susceptibility to ceftriaxone and/or isolates resistant to azithromycin between 2011 and 2016. 6 The Philippines Department of Health -Antimicrobial Resistance Surveillance Program (DOH-ARSP) has been contributing AMR surveillance data to the Western Pacific GASP since 1996 and has not confirmed isolates with decreased susceptibility or resistance to these antibiotics during 2011-2016, 6 while high gonococcal resistance rates against other first-line antibiotics has been long reported ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…6 A recent report showed that 18 of 21 countries in the region reported isolates with decreased susceptibility to ceftriaxone and/or isolates resistant to azithromycin between 2011 and 2016. 6 The Philippines Department of Health -Antimicrobial Resistance Surveillance Program (DOH-ARSP) has been contributing AMR surveillance data to the Western Pacific GASP since 1996 and has not confirmed isolates with decreased susceptibility or resistance to these antibiotics during 2011-2016, 6 while high gonococcal resistance rates against other first-line antibiotics has been long reported ( Figure 1). Ongoing surveillance is thus key to detect potential events of emergence or introduction of resistance to current treatment options.…”
Section: Introductionmentioning
confidence: 99%